236 Effects of mitoquinol during acute heat stress exposure in growing pigs. (30th November 2020) - Mayorga, Edith J; Horst, Erin A; Goetz, Brady M; Rodríguez-Jiménez, Sonia; Abeyta, Megan A; Al-Qaisi, Mohmmad; Lei, Samantha; Rhoads, Robert P; Selsby, Joshua T; Baumgard, Lance H
Abstract: Objectives were to determine the effects of mitoquinol (MitoQ) on performance, metabolism, and inflammation during acute heat stress (HS) in growing pigs. Crossbred barrows (n=32; 59±1 kg BW) where blocked by BW and randomly assigned to 1 of 4 therapeutic-environmental treatments: 1) thermoneutral (TN) control (n=8; TNCtl), 2) TN and MitoQ (n=8; TNMitoQ), 3) HS control (n=8; HSCtl), or 4) HS and MitoQ (n=8; HSMitoQ). The trial consisted of two experimental periods (P). During P1 (2d), pigs were fed ad libitum and housed in TN conditions (20.6±0.1°C). During P2 (24h), HSCtl and HSMitoQ pigs were exposed to continuous HS (35.2±0.03°C); while TNCtl and TNMitoQ remained in TN conditions. Mitoquinol was orally administered twice daily (0700 and 1800 h; 40 mg/d) during P1 and P2. Pigs exposed to HS had increased rectal temperature, skin temperature, and respiration rate (1.46°C, 6.79°C, and 101 bpm, respectively; P< 0.01) compared to their TN counterparts. Acute HS markedly decreased feed intake (67%; P< 0.01). Additionally, HS pigs lost BW compared to their TN counterparts (-4.7 vs. +1.6 kg, respectively; P< 0.01); however, the reduction in BW was less severe in HSMitoQ compared to HSCtl pigs (-3.85 vs. -5.50 kg, respectively; P< 0.01). Circulating glucose increased in HSMitoQ relative to HSCtl pigs (15%; P=0.04). Non-esterified fatty acid (NEFA) concentrations were increased in HS compared to TN pigs (P< 0.01), although this difference was influenced by increased NEFA in HSCtl relative to HSMitoQ pigs (251 vs. 142 μEq/L; P< 0.01). Insulin:feed intake tended to increase in HS relative to TN pigs (P=0.09). Overall, no differences in blood urea nitrogen or cell blood counts were observed across treatments (P >0.10). In conclusion, acute HS exposure negatively altered animal performance and metabolism; however, administering MitoQ appeared to ameliorate the HS response.